New Anti-inflammatory Cyclopeptides From a Sponge-Derived Fungus Aspergillus violaceofuscus - Liu, Jingtang; Gu, Binbin; Yang, Lianjuan; Yang, Fan; Lin, Houwen (Frontiers in Chemistry, 2018)
Three new cyclic peptides including a cyclic tetrapeptide (1), an aspochracin-type cyclic tripeptide sclerotiotide L (2) and a diketopiperazine dimer (3), have been isolated from the ethyl acetate extract of a marine sponge-derived fungus Aspergillus violaceofuscus. The structures of all compounds were unambiguously elucidated on the basis of HRESIMS, 1D and 2D NMR spectroscopic data, MS/MS experiments and chemical methods. Compounds 1 and 3 showed anti-inflammatory activity against IL-10 expression of the LPS-induced THP-1 cells with inhibitory rates of 84.3 and 78.1% respectively at concentration of 10 μM.